Minimising patient harm whilst gaining surgical proficiency - Markar, Sheraz; Lagergren, Jesper (Journal of Thoracic Disease, 2016)
We thank you for the opportunity to respond the this editorial by Dr. Marino and Dr. Weksler, regarding our recently published study (1). Drs. Marino and Weksler make several important inferences from our study, which have implications when considering training in esophageal cancer surgery.